Bibliometric Analysis of Research on Moving Bed Biofilm Reactor - Laili Fitria; Dhuhan Dhuhan (Jurnal Serambi Engineering, 2021)
Waste discharged into the environment (air and water) needs to meet the expectation of environmental quality standards. One method that has been widely studied and to be used in maintaining water quality is a combination of the Moving Bed Biofilm Reactor (MBBR) method. With the Dimensions database, in the last ten years (2010-2020), it is known that there are 373 journals regarding MBBR for wastewater treatment. Furthermore, a bibliometric analysis was carried out with data from 2017 to 2020, using visualization from Vosviewer to determine the development of research on MBBR. Indonesia is in 10th place, contributing five articles on MBBR. Some other countries conducting the most research on MBBR include China, the United States, Iran, India, and Germany. The Journal that publishes the most research on MBBR is Bioresource Technology. The author who has done the most research on MBBR is Olav Vadstein, by the issuance of four articles. Meanwhile, the institutions that write the most research on MBBR are the Norwegian University of Science and Technology and the Technical University of Denmark. Another combination of data-driven systematic literature review (SLR) is needed to complement the bibliometric analysis of the MBBR study for wastewater treatment.